2014
DOI: 10.1038/cdd.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 ablation leads to mitophagy impairment associated with a metabolic shift towards aerobic glycolysis

Abstract: Macroautophagy selectively degrades dysfunctional mitochondria by a process known as mitophagy. Here we demonstrate the involvement of transglutaminase 2 (TG2) in the turnover and degradation of damaged mitochondria. In TG2-ablated cells we observed the presence of a large number of fragmented mitochondria that display decreased membrane potential, downregulation of IF1 along with increased Drp1 and PINK1 levels, two key proteins regulating the mitochondrial fission. Of note, we demonstrate that in healthy mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 54 publications
2
47
0
1
Order By: Relevance
“…Selected VEGF isoforms bind the receptor VEGFR2 and heparan sulfate proteoglycans to stimulate angiogenesis, recently it has been shown that transglutaminase 2 (TG2) enzyme play a role in VEGF165-heparan sulfate proteoglycans interaction (Beckouche et al, 2015). TG2 is a Ca2+-dependent cross-linking enzyme that catalyzes the formation of -␥-glutamyl isopeptide bonds between peptide-bounds glutamine and lysine (Candi et al, 2005;De Laurenzi and Melino, 2001;Liu et al, 2002;Myneni et al, 2015;Rossin et al, 2015;Shrestha et al, 2015). TG2 is highly expressed in endothelial cells, it is located in the cytoplasm and in extracellular space.…”
Section: Transglutaminase 2 In Angiogenesis and Age-related Vascular mentioning
confidence: 99%
“…Selected VEGF isoforms bind the receptor VEGFR2 and heparan sulfate proteoglycans to stimulate angiogenesis, recently it has been shown that transglutaminase 2 (TG2) enzyme play a role in VEGF165-heparan sulfate proteoglycans interaction (Beckouche et al, 2015). TG2 is a Ca2+-dependent cross-linking enzyme that catalyzes the formation of -␥-glutamyl isopeptide bonds between peptide-bounds glutamine and lysine (Candi et al, 2005;De Laurenzi and Melino, 2001;Liu et al, 2002;Myneni et al, 2015;Rossin et al, 2015;Shrestha et al, 2015). TG2 is highly expressed in endothelial cells, it is located in the cytoplasm and in extracellular space.…”
Section: Transglutaminase 2 In Angiogenesis and Age-related Vascular mentioning
confidence: 99%
“…This was proposed to be the result of impaired recruitment of Bax to TG2 À/À mitochondria, resulting in decreased Bax/ANT1 interaction relative to wild-type mitochondria (Malorni et al 2009). A later study from the same group reported that under basal conditions TG2 À/À MEFs (source nor strain background defined) had a large number of fragmented, dysfunctional mitochondria due to an impairment in mitophagy (clearance of defective mitochondria) compared with wild-type MEFs (Rossin et al 2014). TG2…”
Section: Mitochondrial Functionmentioning
confidence: 98%
“…p53 is a well-known oncogene suppressor, and its degradation prevents apoptosis and favors conversely tumor survival and growth (Kang et al 2016). In addition, it must be mentioned that also the metabolism of cancer cells is apparently dependent on the action of Tgase2, as it happens in mammary cancer, in which expression and activity of Tgase2 is eventually relevant for triggering the Warburg effect (Kumar et al 2014;Rossin et al 2015) through NFκB and HIF signaling and more recently through its interplay with PKM2 a key rate limiting enzyme of glycolysis (Altuntas et al 2015). The involvement of Tgase2 in EMT and in angiogenesis is of special relevance for the relationships between Tgase2 and tumor growth.…”
Section: The Pathology: Protective and Aggressive Actions Of Tgase2mentioning
confidence: 99%